2017
DOI: 10.1186/s13293-017-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in insular cortex gyri responses to a brief static handgrip challenge

Abstract: BackgroundCardiovascular disease varies between sexes, suggesting male-female autonomic control differences. Insular gyri help coordinate autonomic regulation and show a sex-dependent response to a sympathetic challenge.MethodsWe examined sex-related insular gyral responses to a short static handgrip exercise challenge eliciting parasympathetic withdrawal with functional magnetic resonance imaging (fMRI) during four 16-s challenges (80% maximum strength) in 23 healthy females (age; mean ± std 50 ± 8 years) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 70 publications
4
11
0
Order By: Relevance
“…A significant factor in determining neural influences on breathing and cardiovascular control in disease conditions is sex; such conditions, including obstructive sleep apnea, heart failure, and congenital central hypoventilation syndrome can show significant injury in cardiovascular and respiratory regulatory brain sites ( Kumar et al, 2012 ; Kumar et al, 2015 ; Macey et al, 2008 ; Macey et al, 2012b ; Ogren et al, 2014 ), but that injury frequently differs substantially between males and females, especially in limbic areas ( Macey et al, 2012a ). Moreover, responsiveness of affected brain sites to evoked pain or blood pressure challenges significantly differs between sexes ( Henderson et al, 2008 ; Macey et al, 2016 ; Macey et al, 2017 ). The mechanisms underlying these pattern differences between males and females are unclear, but there is a potential for sex-related protective mechanisms and consequent injury differences to exist in GTCS, where analogous exposure to hypoxic and extreme blood pressure changes are common in the condition.…”
Section: Discussionmentioning
confidence: 99%
“…A significant factor in determining neural influences on breathing and cardiovascular control in disease conditions is sex; such conditions, including obstructive sleep apnea, heart failure, and congenital central hypoventilation syndrome can show significant injury in cardiovascular and respiratory regulatory brain sites ( Kumar et al, 2012 ; Kumar et al, 2015 ; Macey et al, 2008 ; Macey et al, 2012b ; Ogren et al, 2014 ), but that injury frequently differs substantially between males and females, especially in limbic areas ( Macey et al, 2012a ). Moreover, responsiveness of affected brain sites to evoked pain or blood pressure challenges significantly differs between sexes ( Henderson et al, 2008 ; Macey et al, 2016 ; Macey et al, 2017 ). The mechanisms underlying these pattern differences between males and females are unclear, but there is a potential for sex-related protective mechanisms and consequent injury differences to exist in GTCS, where analogous exposure to hypoxic and extreme blood pressure changes are common in the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have dealt with gender-related differences in the three main neural reflexes which adjust the cardiovascular system during exercise. To the best of our knowledge, there is only one study addressing the potential differences between males and females in central command activation [ 74 ]. In this research conducted during static handgrip, authors found sex-related different patterns of activation in insular gyral responses.…”
Section: Gender-related Differences In Central Command Exercise Presmentioning
confidence: 99%
“…In healthy adults, we showed the functional organization of the insular cortex is gyri-specific for the handgrip, a challenge that combines autonomic perturbation and an intentional motor activity [ 46 , 47 ]. Specifically, the anterior insula is more activated during the early, predominantly parasympathetic withdrawal phase [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the strain phase of the handgrip challenge, which is associated with a moderate HR and sympathetic increase, elicited the greatest responses in the middle insular gyri. These sex-specific neural patterns co-occur with sex-specific peripheral differences, with females displaying HR smaller increases [ 3 , 47 ]. The data are consistent with a recent human study showing tachycardic responses elicited by stimulating the posterior insula and bradycardic responses from stimulating the more anterior insular cortex [ 50 ].…”
Section: Introductionmentioning
confidence: 99%